2010
DOI: 10.1371/journal.pone.0009689
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid-Induced Arrhythmia Is Mediated by Muscarinic M2 Receptors in Neonatal Rat Cardiomyocytes

Abstract: BackgroundIntrahepatic cholestasis of pregnancy (ICP) is a common disease affecting up to 5% of pregnancies and which can cause fetal arrhythmia and sudden intrauterine death. We previously demonstrated that bile acid taurocholate (TC), which is raised in the bloodstream of ICP, can acutely alter the rate and rhythm of contraction and induce abnormal calcium destabilization in cultured neonatal rat cardiomyocytes (NRCM). Apart from their hepatic functions bile acids are ubiquitous signalling molecules with div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
101
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 44 publications
10
101
1
3
Order By: Relevance
“…In addition, the concentrations were significantly reduced compared to previously published work (Gorelik et al, 2002;Miragoli et al, 2011a;Sheikh Abdul Kadir et al, 2010;Williamson et al, 2001). …”
Section: A N U S C R I P Tcontrasting
confidence: 61%
“…In addition, the concentrations were significantly reduced compared to previously published work (Gorelik et al, 2002;Miragoli et al, 2011a;Sheikh Abdul Kadir et al, 2010;Williamson et al, 2001). …”
Section: A N U S C R I P Tcontrasting
confidence: 61%
“…In brief, BAs have the capacity to signal via nuclear and G protein-coupled receptors, including G protein-coupled bile acid receptor 1 (GPBAR1), as well as, large conductance Ca 21 activated potassium channel K Ca 1.1 (BK Ca ) (Dopico et al, 2002) and muscarinic receptors (Sheikh Abdul Kadir et al, 2010) in which myriad effects on cardiovascular function have been demonstrated, including changes in myocyte contraction and synchronization (Bogin et al, 1983;Gorelik et al, 2002;Sheikh Abdul Kadir et al, 2010), vasodilation in a number of ex vivo isolated vascular models (Pak and Lee, 1993;Pak et al, 1994;Dopico et al, 2002;Bukiya et al, 2007;Sheikh Abdul Kadir et al, 2010), and bradycardia in vivo (Joubert, 1978a,b). In addition, BA dx.doi.org/10.1124/jpet.113.210005. s This article has supplemental material available at jpet.aspetjournals.org.…”
Section: Introductionmentioning
confidence: 99%
“…However, bile acids also act through other receptors including muscarinic receptors, the sphingosine-1-phosphate receptor 2, ␣ 5, ␤ 1-integrin, through signal transduction pathways such as those mediated by Jun Nterminal kinase (JNK), ERK, and Akt ( 3,(6)(7)(8), and through posttranslational interactions with proteins ( 9 ). Signaling via these diverse pathways is regulated in part by the local concentration and chemical structure of the bile acid species, which in turn is controlled by hepatic synthesis, host and microbial metabolism, and the enterohepatic circulation.…”
mentioning
confidence: 99%